Genetic variation for agronomic and floral traits in prospective maintainer and restorer lines selected from coastal rice collections in Bangladesh (Annals of Bangladesh Agriculture, 2025)
The identification of stable maintainer and restorer lines strengthens sustainable hybrid rice technology to increase its production and support the self-sufficiency of food in Bangladesh. Experiments were conducted to assess the genetic variation among 47 prospective maintainer and restorer lines selected from coastal rice collections in the Genetics and Plant Breeding experimental field and laboratory of Gazipur Agricultural University, Gazipur during 2021-2023. Most of the Agronomic and floral traits were significantly (P